The status of actual nutrition in students of boarding physical training school - O.B. Plastunova; S.L. Nyankovskyy (Zaslavsky O.Yu., 2018)
Background. The status of nutrition in child athletes representing various sports, which vary in load levels, remains insufficiently studied. The purpose of the study was to assess the status of the actual nutrition in students of boarding physical training school and to develop recommendations for its optimization. Materials and methods. The energy value and the nutrient composition of the food rations of the students were calculated according to the 28 menu layouts of the autumn and spring seasons. Results. Actual nutrition of students is irrational, unbalanced, especially in the content of vitamins and minerals, undifferentiated depending on the sports, gender and age of students, changeable in energy value, nutrient composition and mode on different days of the week, with the lowest energy value and content of nutrients on Saturday and Sunday. Conclusions. Nutrition of girls of all sports and age groups under study, as well as boys - shooters, archers, water polo players, wrestlers of all age groups (metabolic equivalent of task (MET) ≤ 4.0), 12-14-year-old boxers, lugers, fencers (MET 5.0-6.0) and 12-13-year-old representatives of pentathlon, cycling, football, athletics and rowing (MET > 6.0) is excessive, nutrition of 15-17-year-old boys representing various sports with MET > 6.0 is insufficient in energy value, content of proteins, fats and carbohydrates.